The Application of Digital Solutions in Public Administration: The Evidence from Poland - Tomasz KAFEL; Angelika WODECKA-HYJEK; Rafal KUSA (Communications of International Proceedings, 2021)
The aim of this study is to explore the digitalization of public administration. In particular, this study aims to identify digital technologies that are most commonly utilized in public organizations in Poland. Moreover, this study aims to unveil the differences in the application of digital solutions among different types of public organizations. This study employs a quantitative survey and case study method. The results of the survey show that digital solutions are used to a different degree and that different types of public organizations utilize digital solutions in different ways and to different extend. The results indicate that the most common tools implemented in public administration in Poland are electronic register box, electronic document circulation, electronic handling of human resources matters, online meetings, online courses, internal virtual network drives, electronic working time recorders, and social media in contacts with the stakeholders. Among examined types of public organizations, the Social Insurance Institution (SII) exhibits the highest level of digital solutions implementation which is higher than in any other type of public organization, as well as the average level observed in the entire sample. This advantage is visible in all examined areas of digitalization, namely internal processes, external processes, and supporting solutions. This study offers meaningful implications for public administration managers, including the example of good practices implemented in the SII.
Keywords: Digitalization; IT; Public Administration; E-Government.